Pola Asuh dan Strategi Orang Tua dalam Mengelola Sosial Media pada Anak Usia Dini - Zahra, Afifah; Harahap, Sartika Dewi; Mukhlis, Mukhlis (Prodi Pendidikan Keagamaan Islam, 2023)
This study aims to describe parenting strategies in managing social media use among early childhood children in Kelurahan Pidoli Dolok. The widespread use of social media has become a significant challenge for parents, especially during early childhood a developmental stage that is highly vulnerable to digital influences. This research employed a descriptive qualitative approach, using in-depth interviews with 20 parents who have young children. The findings reveal that parents apply three main parenting styles: democratic, authoritarian, and permissive. The democratic parenting style is the most commonly applied and has a positive impact on various aspects of child development, including cognitive, social-emotional, language, and moral-spiritual growth. In contrast, authoritarian parenting tends to restrict children's expression and limits their social media use without sufficient explanation, while permissive parenting allows excessive freedom without supervision, leading to negative consequences such as gadget addiction, emotional disturbances, and weakened moral understanding. These findings highlight the importance of active parental involvement in supervising and guiding children's media use, so that social media can be utilized positively to support holistic child development.